Investment and Usage of New Technologies: Evidence from a Shared ATM Network - Ferrari, Stijn; Verboven, Frank; Degryse, Hans (American Economic Review, 2010)
The success of new technologies depends on both the firms' investment and consumers' usage decisions. We study this problem in a shared ATM network. Inefficiencies may arise because banks coordinate investment, and consumers may not make proper use of the network. Based on an empirical model of ATM investment and demand, we find that banks substantially underinvested in ATMs, in contrast with earlier findings of strategic overinvestment in the United States. Furthermore, ATM usage was too low, because regulation prohibited fees for cash withdrawals. A direct promotion of investment improves welfare, but fees for branch cash withdrawals would be more effective. (JEL G21, G31, O33)